Anomalies in relationships between securities' yields and yield-surrogates - Ball, Ray (Journal of Financial Economics, 1978)
A literature survey reveals consistent excess returns after public announcements of firms' earnings. If the information in publicly-announced earnings is a public good, then these results seem inconsistent with equilibrium in the securities market: public goods, being without private cost, should earn no private return. Alternative explanations of this anomaly are considered. The most likely explanation is that earnings variables proxy for omitted variables or other misspecification effects in the two-parameter model: that the measured market portfolio is not mean-variance efficient. Similar anomalies and explanations apply to other ‘yield-surrogates’, including dividend yields and Value Line ratings.